(untitled) (Research, Society and Development, 2020)
Objective: To perform a literature review addressing the main fundamentals and applications about indirect restorations of CR in posterior teeth. Methods: A bibliographic review of studies available in the literature published in the last 10 years was carried out by searching electronic databases with the selected descriptors and following the inclusion and exclusion criteria of the studies. Literature review: In general, the indirect restorations of CR are those performed outside the oral cavity, either in the office or in the laboratory and which is then cemented to the tooth with resin or conventional cements. With the advent of indirect RC restorations, several commercial brands have emerged to be used in these restorations. The main objective is to obtain the highest degree of conversion possible, improving the mechanical properties and increasing the longevity of these restorative procedures. Conclusion: Indirect and semi-direct restorations made with CR are excellent alternatives for cases in which direct restorations have limitations in their manufacture. However, for an adequate choice of technique, it is important to observe the patient’s needs as well as the professional’s preferences and skills.